A Novel IUD Platform Design Uses a Flexible Nitinol Frame to Deliver Either Copper or Levonorgestrel: Phase 2 Data [03I]. (May 2020) - Turok, David Keith; Peters, Kevin; Katz, Bob
Abstract : INTRODUCTION: Current IUD applicators vary among copper and levonorgestrel devices. We present data on a new intrauterine contraceptive platform that uses a flexible nitinol frame provided in a preloaded applicator with precut strings and a tapered leading edge to deliver either low-dose copper (175 mm 2 ) or a levonorgestrel (52 mg) IUD. METHODS: Two Phase 2 studies provide information, one for copper and the other for the levonorgestrel IUD. Subjects met standard inclusion & exclusion criteria for each IUD, per the CDC. IUD placement occurred any day in the menstrual cycle. The primary outcome for both studies was efficacy, measured by Pearl Index (PI). Secondary outcomes include placement success, ease, and pain as well as overall tolerability and safety. RESULTS: The copper and levonorgestrel IUD studies enrolled 286 and 279 women, respectively; 60.8% and 64.2% were nulliparous. Investigators described IUD placements as "easy" or "very easy" in 91.5% and 88.9%, while participants rated pain as "moderate" or "very painful" in 19.0% and 21.5%, respectively. Placement required cervical dilation in 41 (14.5%) and 42 (15.1%); 99% of placements were successful in both studies. One pregnancy occurred in the Copper IUD study (PI=0.73, 95% CI 0.09-2.65) and none in the levonorgestrel study (PI=0.0, 97.5% confidence upper bound=1.88). We identified no uterine perforations. First year expulsions occurred in 1 (0.4%) and 7 (2.5%) participants. CONCLUSION: This novel IUD platform design successfully delivers both a low dose copper and levonorgestrel IUD with promising efficacy and safety data.